Characterization of Indium addition on Sn-Bi-Sb Lead free Solder alloy - Mahlab, Sara Mosaad; Kamal, Mustafa; Mansour, Abd El-Raouf mohamed (JOURNAL OF ADVANCES IN PHYSICS, 2016)
The aim of these work is to measure the effect of the addition of In with different atomic percent weight on structure, melting, Electrical and mechanical properties of Sn70-X at.% -Bi15 at.% -Sb15 at.%- Inx at.% rapidly solidified. X-ray diffraction analysis (XRD), differential scanning calorimetry (DSC), temperature dependence of resistivity (TDR), and mechanical resonance method are performed. It’s found that electrical conductivity (Ïƒ) and thermal conductivity (K) increased gradually by increasing In at.%. Melting temperature reduced from 470.12 K for Sn70 at.%- Bi15 at.%- Sb15 at.% to 427.13 K in Sn61 at.%- Bi15 at.%- Sb15 at.%- In9 at.%. Also, elastic moduli, internal friction and thermal diffusivity measured from melt-quenched ribbons.